Venovenous extracorporeal membrane oxygenation to treat hypercapnia in a morbidly obese patient (Swiss Medical Weekly, 2018)
Morbid obesity plays an increasingly important role in healthcare. Patients who are severely obese often suffer from a range of medical problems. One problem is obesity-related hypoventilation syndrome with its resulting hypercapnia. We report a case of a 33-year-old female patient who was in an extraordinarily bad medical state, with severe hypercapnia (pCO2 15.1 kPa), sepsis, acute anuric kidney failure and resulting acidosis (pH 6.96). Her body mass index was 84 kg/m2. Her chances of survival were considered very low after failed attempts at noninvasive ventilation. Based on prior research, we refrained from intubation and chose venovenous extracorporeal membrane oxygenation to treat the hypercapnia. In the entire medical literature, we are not aware of a similarly extraordinary case of obesity-related hypoventilation syndrome that could finally be treated successfully. The idea behind this case report is to consider venovenous extracorporeal membrane oxygenation as an alternative to intubation in this patient collective.